Role of intentions and information structure in a gift-exchange game : An experimental study - Polívka, Martin; Miklánek, Tomáš; Chytilová, Helena; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2020)
This diploma thesis deals with the importance of intentionsand the role of information in people’s decision-making. The theoreticalpart presents different models of social preferences and their possibleshortcomings, together with real-world consequences. It also outlinesthe possible role of game complexity in decision-making. Data used foranalysis are collected via the laboratory experiment using a within-subjectdesign. The experiment follows the idea behind the design that was firstproposed by Charness and Levine (2007). It introduces the stochasticfactor into gift-exchange game and thus allows reaching the node withthe same payoff through two different paths. This allows to isolate effectof intentions and compare the effort levels of the workers. I found thatworkers are responding positively when their wage is a result of high wageand bad luck but are willing to punish the firm in the case of low wage andgood luck. These results suggest that outcome-based models that takeinto account only distributional concerns may not be able to explain thedifferences in effort levels, and intentions based models may, therefore, bemore suitable for the description of decision-making in various economicgames. I also report mixed results concerning the effect of the gameenvironment’s complexity on the effort choices of workers.
Vedoucí práce: Tomáš Miklánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses